Effects of Shape and Orientation of Pore Canals on Mechanical Behaviors of Lobster Cuticles. (21st June 2018) - Lin, Shiyun; Chen, Bin; Fang, Zhongqi; Ye, Wei
Abstract: The work is to investigate the relationships between the microstructures and mechanical behaviors of lobster cuticles and reveal the inner mechanisms of the anisotropic mechanical properties of the cuticles and give the helpful guidance for the design of high-performance man-made composites. First, the tensile mechanical properties of the longitudinal and transverse specimens of the cuticles of American lobsters were tested with a mechanical-testing instrument. It is was found that the fracture strength and elastic modulus of the longitudinal specimens are distinctly larger than those of the transverse specimens. Then, the microstructural characteristics of the fracture surfaces of the specimens were observed with scanning electron microscope. It was observed that the pore canals in the cuticles are elliptic and their orientations are along the longitudinal orientation of the cuticles. Furthermore, the stresses and micro-damage of the longitudinal and transverse specimens were calculated with the rule of progressive damage by finite element method. It was revealed that the shape and orientation of the pore canals in the cuticles give rise to the anisotropic mechanical property of the cuticles and ensure that the cuticles possess the largest fracture strength and elastic modulus along their largest main-stress orientation.